The relationship between diet patterns and physical activity with the incidence of overweight in adolescents at SMAN 8 Maros - Firdhawati; St Masithah; Siti Uswatun Hasanah; Andi Rahmaniar MB (Indonesian Nutrition Association, 2026)
Background: Adolescents are a vulnerable age group prone to nutritional problems, particularly overweight and obesity, which often result from an imbalance between energy intake and energy expenditure. Dietary patterns high in energy and fat but low in fiber, combined with insufficient physical activity, contribute to the rising prevalence of overweight and obesity. Preliminary data at SMAN 8 Maros showed that 10.13% of students were overweight and 9.03% were obese. Objective: This study aimed to examine the relationship between dietary patterns and physical activity with the incidence of overweight among adolescents at SMAN 8 Maros. Methods: This research employed a quantitative design with a case-control approach. A total of 82 students from grades X and XI were selected using simple random sampling, with a 1:1 ratio between the case group (41 students with overweight/obesity) and the control group (41 students with normal nutritional status). Dietary data were collected using 2x24-hour food recall and Food Frequency Questionnaire (FFQ), while physical activity was measured using the Global Physical Activity Questionnaire (GPAQ). Data were analyzed using the Spearman rank correlation test. Results: Statistical analysis revealed a significant relationship between dietary intake including energy (p=0.000), protein (p=0.006), fat (p=0.008), and carbohydrate (p=0.002)—and the incidence of being overweight. In contrast, no significant association was found between the frequency of main meal and processed food consumption (p=0.828 & p=0.824) and overweight incidence. Physical activity demonstrated a significant correlation (p=0.002) with being overweight. Conclusion: Dietary intake (energy, protein, fat, carbohydrates) and physical activity are significantly associated with being overweight among adolescents. However, no significant relationship was observed between meal frequency and overweight incidence among adolescents at SMAN 8 Maros.